Linguistic and cultural character of words in Kazakh and Turkish linguistic etiquette - Kasymova, А.А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
The article deals with linguistic units, that is, words expressing the etiquette of farewells in Kazakh and Turkish. In addition, linguistic units have been grouped according to various characteristics. Comparative analysis shows that linguistic units, which represent a common cultural meaning, determine the national picture of the world picture.